193 CONNECTED HEALTH SUSTAINING HOME STAY IN DEMENTIA (CHESS): HEALTH-RELATED QUALITY OF LIFE IN CAREGIVERS OF PEOPLE WITH DEMENTIA. (25th October 2022) - Blake, C; Merriman, N; Mackey, L; Fernandez, EG; Curran, F; Caulfield, B; O'Shea, D; Doyle, R; Power, D
Abstract: Background: Caregivers of People with Dementia (PwD) can experience high levels of distress, which can negatively affect their physical and psychological well-being. We explored factors that influence Health-Related Quality of Life (HRQoL) of caregivers of PwD over 12 months. Methods: Fifty-two PwD and their informal caregivers were recruited by convenience sampling to the "CHESS" Study. Data were collected at five time points over 12 months between April 2017 and November 2019. Mixed model analyses were used to investigate associations of caregiver HRQoL (measured by the EuroQol Visual Analogue Scale; EQVAS) with factors in four domains: 1) Psychological Well-Being (PWB; measures of anxiety, depression, and caregiver distress); 2) Social Capital and Resources (SCR; incorporating access to community-based health services, transportation needs, education level, occupation and living situation of the PwD, and employment status of the caregiver); 3) Physical Fitness and Health (PFH; including the Quantitative Timed Up and Go (QTUG), baseline grip strength, indices of frailty, sensory acuity); and Managing Everyday life with Dementia (MED; incorporating measures of cognition, behavioural disturbances, functional ability, and indices of dependence of PwD. Results: In the PWB domain, greater levels of caregiver depression (p<0.001) and a greater change over time in caregiver distress related to PwD behavioural disturbances (p=0.008) predicted lower caregiver HRQoL. In the PFH domain, HRQoL was lower for caregivers of PwD who were frail (p=0.04) and had severe comorbidities (p=0.037). None of the factors within the SCR or MED domains reached significance. Conclusion: This longitudinal analysis elucidates potential predictors of HRQoL in caregivers of PwD. In particular, caregiver depression and distress related to behavioural disturbances in PwD were shown to significantly impact on HRQoL ratings. Caregiver interventions should be tailored to include support for psychological well-being.